Children’s perceptions of participation: a study using Forum Theatre - Markogiannaki, Angela (2016)
Over the recent years there has been growing acceptance that eliciting and advocating the voice of children is of great importance directly connected to the work of social workers. There is extensive literature on the benefits of child participation which include strengthening personal and social development and promoting a more democratic society. However there is reason to believe that child participation is somewhat ineffective. To tackle this, adults have to be aware of their responsibilities but the lack of awareness and thus literature on what children think when it comes to participation should be addressed. Using an experimental Forum Theater method, this study strives to elicit the views on children on their understanding and exercise of their right to participate. Overall 10 children aged 6-12 participated in three Forum Theatre workshops that resulted in a Forum Theater play which was presented three times to an audience, the results of which are described and analyzed. Content analysis and in vivo coding was used to present the children’s views and the underlying emancipatory processes they go through. The results of this study add to previous literature demonstrating that children are capabilities of understand and exercising participation as a right, as a form of citizenship and as an act of empowerment stressing at the same time in the need for a safe place where children can be encouraged to reflect but also be empowered to take action for change. The importance of co- learning between youth and adults that can facilitate critical dialogue, awareness and skills that lead to critical consciousness is also emphasized. This study is an exemplar of an innovative, democratizing and effective methodology that might profitably be utilized in social work with children and families. Finally, departing from the findings suggestions are made as to how child participation can be made to be more effective.